Management of Perinatal Iron Deficiency Anemia: A Retrospective Review of a Community Based Intervention [18P]. (May 2018) - Fernandes, Samantha; Darbinian, Jeanne; Postlethwaite, Debbie; Shirazi, Aida; Mandel, Sarah
Abstract : INTRODUCTION: Unresolved iron-deficiency anemia in pregnancy contributes to maternal and neonatal morbidity, which may be preventable by iron administration. Kaiser Permanente San Francisco (KPSF) Perinatal Anemia Management Program (PAMP) developed a comprehensive algorithmic approach to identify and treat iron-deficiency anemia. A retrospective observational study was conducted to assess the impact of PAMP on peripartum anemia prior (1/2012-6/2013), during (9/2013-2/2015) and after (3/2015-8/2016) its implementation. METHODS: Iron-deficient anemic pregnant women delivering at KPSF were identified during the above time periods and divided into cohorts who received prenatal care at KPSF, exposed to PAMP versus KPSF satellites, not exposed to PAMP. Data for 2nd, 3rd trimester and delivery hemoglobin values, parenteral iron administrations and blood transfusions were electronically extracted and analyzed using Chi-square statistics, t-tests, ANOVA, and non-parametric tests to compare differences among groups. RESULTS: The mean % change in hemoglobin was significantly higher during-PAMP and post-PAMP among women receiving prenatal care at KPSF compared to women who received prenatal care at satellites (PAMP: 14.6 vs. 12.7, p<0.01; post-PAMP: 15.2 vs. 13.1, p<0.01). The number of KPSF women receiving parenteral iron was highest during PAMP (n=63) and remained constant for satellite women for the three time periods (n=4). Finally, the number of blood transfusions sequentially decreased by period regardless of place of prenatal care (pre-PAMP: n=25, PAMP: n=13, post-PAMP: n=11). CONCLUSION: The PAMP comprehensive approach was associated with improvements in peripartum iron-deficiency anemia, increased parenteral iron administration and a decrease in blood transfusions. Implementation of similar programs may in turn lower maternal and neonatal morbidity.